Failure of democratization: comparative case study of Russia and Turkey - Razminoviča, Daira (Riga Graduate School of Law, 2018)
Purpose of this thesis is to understand, why states fail the process of democratization and to compare the development of the democratization process in Russia and Turkey. Taking into consideration that a constitution is the core of a state, the thesis seeks to find out whether the constitutions of the aforementioned states create mechanisms that promote deviation from a democratic regime.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Russia; Turkey